2017
DOI: 10.1038/jp.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hemodynamics before, during and after elective cesarean section under spinal anesthesia in low-risk women

Abstract: Significant hemodynamic changes (reduction of TPR and increase of CO) take place at the time of delivery of fetus and placenta. Knowledge of normal hemodynamic values using a reliable noninvasive technique during various stages of pregnancy and the postpartum period is feasible, and might assist clinicians in assessing the level of patient deviation from expected cardiac performance, especially in high-risk women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Contrary to past studies that showed an increase in CO after vaginal or cesarean delivery (most probably due to autotransfusion of uterine blood into the maternal systemic circulation and the administration of oxytocin), 7,27 removal of the fetus during elective cesarean sections in our study caused a marked decrease in CI, due to an increase in TPRI and a resultant decline in preload and SI.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to past studies that showed an increase in CO after vaginal or cesarean delivery (most probably due to autotransfusion of uterine blood into the maternal systemic circulation and the administration of oxytocin), 7,27 removal of the fetus during elective cesarean sections in our study caused a marked decrease in CI, due to an increase in TPRI and a resultant decline in preload and SI.…”
Section: Discussioncontrasting
confidence: 99%
“…While this finding is refuted by previous study, 8 it is supported by a recent study in a similar population of parturients. 27 We hypothesize that the lack of decrease in TPRI after regional anesthesia may be attributed to the fact that the preoperative measurements were taken prior to entry into the operating room. At this point, the patient was at resting state, with a mean heart rate of 85.2 AE 13.9 bpm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prospective longitudinal observational study was performed at a tertiary medical center. All the women were assessed for hemodynamic changes using the NICaS™ device while lying in the supine position with leftward tilt, as recently described by us [ 17 , 18 ], and at the following time points: 15–30 min before undergoing a CS (measurement #1), immediately after receiving spinal anesthesia (measurement #2), immediately after delivery of the newborn and the placenta (measurement #3), at the closure of abdominal fascia (measurement #4), within 24–36 h (measurement #5), and 48–72 h postpartum (measurement #6).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been performed using invasive and non‐invasive devices during Cesarean section, but none has compared a non‐invasive device to the current clinical standard of monitoring maternal hemodynamic parameters during high‐risk Cesarean section. Furthermore, most published studies have relied on percentage error or difference to evaluate or compare monitors, even though such a comparison is inappropriate when a gold‐standard invasive monitoring method is lacking.…”
Section: Discussionmentioning
confidence: 99%